Missing the mark : gathering better data from student-athlete exit interviews - Strode, James; Davies, Melissa, active 2020; Lawrence, Heather J. (London : Human Kinetics, Inc., 2020)
A great deal of sport management literature in recent years draws upon the need for effective quantitative and qualitative research methods. However, there are limited cases for a sport management faculty to effectively teach students proper process, design, and implementation of survey or interview research, particularly for real-world sport applications, such as student-athlete exit interviews. This case aims to fill this gap and outlines a plan for students to identify limitations in current student-athlete exit data collection methods and to learn the common barriers associated with effective research design. Students are made aware of common missteps throughout the research process and are provided foundations for effective survey and interview design. Information taught via this case can also be used across sport management contexts, such as fan experience surveys, retail customer satisfaction surveys, or donor satisfaction interviews.
Originally Published InStrode, J., Strode, M., & Lawrence, H. J. (2020). Missing the Mark: Gathering Better Data From Student-Athlete Exit Interviews. Case Studies in Sport Management, 9(1), 25-31.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; National Collegiate Athletic Association -- Case studies; Exit interviewing -- Case studies; Management -- Case studies